Reducing emissions of the fast growing Vietnamese coal sector: The chances offered by biomass co-firing. (1st April 2019) - Truong, An Ha; Patrizio, Piera; Leduc, Sylvain; Kraxner, Florian; Ha-Duong, Minh
Abstract: Vietnam's Power Development Plan 7A authorized many new coal power plants projects, implying an increase of greenhouse gases emissions from 90 MtCO2 eq/year today to 360 MtCO2 eq/year in 2030. How could co-firing technology –that is the partial substitution of coal by biomass– contributes to mitigate that problem? In this study, we assess the costs and potentials of co-firing rice residues in present and planned coal power plants in Vietnam using a spatially explicit optimization model: BeWhere, adapted as recursive annual dynamic. We found that, the cost of CO2 emissions is the key parameter determining at what level the technology is used. A cost of CO2 emissions of 8 /tCO2 mobilizes the maximum technical potential of the rice straw and husk domestic resource, with an annual emission reduction of 28 MtCO2 eq/year by 2030. At this level, biomass co-firing contributes to an 8% emission reduction in the coal power sector with the abatement cost of 137 Million USD. Highlights: Vietnam can reduce CO2 emissions from coal power plants by co-firing rice residues. The maximum technical potential is an 8% reduction compared to Business As Usual. Co-firing viability require carbon credits or a renewable portfolio standard.